Management of scad fisheries (Decapterus spp.) in Sulawesi Sea Waters, North Sulawesi Province, using EAFM - Puansalaing, Deysy M.; Budiman, Johnny; Boneka, Farnis B.; Makapedua, Daisy M.; Lasut, Markus T.; Ngangi, Edwin L.A.; Sumilat, Deiske A.; Darmono, Oktaviano P. (Universitas Sam Ratulangi, 2021)
There are a large variety and quite abundant types of small pelagic fish that have high economic value in the Sulawesi Sea. One of which is the blue scad fish or commonly known as malalugis (Decapterus macarellus). This study aims to analyze and determine the status of scad fisheries management and to develop recommendations in the management of scad fisheries in the waters of Sulawesi Sea, North Sulawesi Province. The evaluation of fishery management status is carried out using multi-criteria analysis (MCA) through the development of composite index of each indicator of Ecosystem Approach to Fisheries Management (EAFM). The results showed that, in general, the status of scad fisheries management in North Sulawesi Province, was in â€˜goodâ€™ category, specifically reviewed from the domain of fish resources fall into the category of â€œmediumâ€, habitat and ecosystem â€œgoodâ€, fishing techniques â€œgoodâ€, economy â€œnot goodâ€, social â€œmediumâ€ and institutional â€œgoodâ€. Management actions take precedence over domains that have â€œpoorâ€ indicator values. Priority management action is implemented in the economic domain, followed by the domain of fish resources, social, institutional and fishing techniques.Indonesian title: Pengelolaan perikanan ikan layang (DecapterusÂ spp.) di perairan Laut Sulawesi, Provinsi Sulawesi Utara, menggunakan EAFM